PENGARUH KAYU MANIS TERHADAP PENURUNAN TEKANAN DARAH PASIEN HIPERTENSI DI PUSKESMAS TALAGA JAYA - Fitria Handayani; Ibrahim Paneo (-, 2021)
Hypertension is a disease that effecting of high morbidity. The aim of this research is to determine the influence of employing cinnamon boiled to decrease of blood Pressure toward hypertension patients in Talaga Jaya Health Center. This research is a quantitative and the design of research is used Quasi Experiments Pre-Post Test. The population are 30 people. The sampling technique is Total Sampling. The results showed both systolic and diastolic hypertension was decreased after employed cinnamon boiled for 3 days in a row. (P<0.05) was concluded which means that there was an influence of employing cinnamon boiled to decrease of blood pressure toward hypertensive patients in Talaga Jaya Health Center.